Democratic backsliding as a catalyst for polity-based contestation?: populist radical right cooperation in the European Parliament - Chiru, Mihail (Journal of European public policy, 2023)
The strengthening of the populist radical right poses an important challenge for European integration. This article explores whether democratic backsliding among member states has acted as a catalyst for broader PRR cooperation at the EU level. Studying the co-sponsorship and contents of parliamentary questions and roll-call vote cohesion of PRR representatives in the European Parliament from 2009 to 2019, we examine the extent and substance of their joint polity-based contestation of European integration. Our findings indicate that overall levels of PRR cooperation remain low and concentrated within European party groups, suggesting that ideological divergences between PRR actors and their institutional fragmentation within the EP still hamper their formal cooperation at the European level. These insights feed into debates on the potential and limitations of transnational cooperation of PRR actors.